Enhancing root traits and quality of sorghum and guar through mixed cropping and nutrient management - BHAKAR, ANKUR; SINGH, MAGAN; KUMAR, SANJEEV; KUMAR, DINESH; MEENA, B L; MEENA, V K; SINGH, Y V (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted at ICAR- National Dairy Research Institute, Karnal during 2018-19 to study the effect of mixed cropping and nutrient management on root traits, nutritional quality and yield of sorghum and guar fodder crops. Experiment was laid out in factorial randomized complete block design with four seed rate combinations in different ratios of sorghum and guar along with six nutrient management treatments in three replications. Results showed that the root traits, viz. root length, volume and dry weight were higher under mixed cropping in comparison to sole crops however the difference was not significant, whereas the significant difference were observed in root traits under different nutrient management practices. Statistically higher green fodder yield was reported under sole sorghum but it was at par with 75% sorghum + 25% guar. Nutritionally enriched fodder with higher macro and micronutrients was also obtained under 75% sorghum + 25% guar treatment. Under mixed cropping nutrient uptake and soil nutrient status at crop harvest were higher in comparison to sole crops. Results pertaining to nutrient management practices revealed that higher supply of nutrients under 100% RDF, 100% RDF +PGPR, 100% RDF +seaweed extract and 75% RDF +seaweed extract treatments helped the crops to take up more nutrients besides leaving substantial balance in the soil at harvest. It was concluded that 75% sorghum + 25% guar mixed cropping with 75% RDF + seaweed extract was best combination to get higher and nutritionally enriched fodder and enriched soil at harvest.